Robust electromagnet design for pulse forming application. Issue 2 (4th March 2019) - Dond, Shantaram; Choudhary, Hitesh; Kolge, Tanmay; Sharma, Archana; Dey, G.K.
Abstract : Purpose: An electromagnet that can produce strong pulsed magnetic fields at kHz frequencies is potentially very favourable to exert a Lorentz force on the metallic workpiece. One of the applications of the pulsed magnetic field is the electromagnetic forming where the design of robust electromagnet is critical. The purpose of this paper is to design a robust electromagnet (coil) for high velocity electromagnetic tube forming operation. Design/methodology/approach: First of all, an analytical model is developed to design the electromagnet and predict the aluminium tube velocity under the action of the estimated pulsed magnetic field. Next, the finite element-based numerical model is used to test the robustness of the designed coil and validate the analytical model. The coil is fabricated and implemented for free forming of aluminium tube. Experimental results of tube displacement are further compared with numerical and analytical model results. Findings: The experimental tube displacement results are showing a good match with analytical and numerical results. The designed electromagnet has generated a peak magnetic field around 14 T at 20 µs rise time and deformed the aluminium tube with a peak velocity of 160 m/s. Robustness of the electromagnet under the action of forming stress is insured by numerical stress analysis and experiments. Practical implications: Though the designed model in this work is for the 2.4 mm aluminium tube forming, it can also be used for different tube materials, tube dimensions and other electromagnetic forming applications with some modifications. Originality/value: The research results provide powerful theoretical, numerical simulation and experimental support for the robust electromagnet design.